Five regions, five retinopathy screening programmes: a systematic review of how Portugal addresses the challenge - Pereira, A.; Laureano, R.M. S.; Neto, F. (BMC Health Services Research, 2021)
Background: The implementation of a population-based screening programme for diabetic retinopathy involves several challenges, often leading to postponements and setbacks at high human and material costs. Thus, it is of the utmost importance to promote the sharing of experiences, successes, and difficulties. However, factors such as the existence of regional programmes, specificities of each country’s health systems, organisational and even linguistic barriers, make it difficult to create a solid framework that can be used as a basis for future projects. Methods: Web of Science and PubMed platforms were searched using appropriate key words. The review process resulted in 423 articles adherent to the search criteria, 28 of which were accepted and analysed. Web sites of all Portuguese governmental and non-governmental organisations, with a relevant role on the research topic, were inspected and 75 official documents were retrieved and analysed. Results: Since 2001, five regional screening programmes were gradually implemented under the guidelines of Portuguese General Health Department. However, complete population coverage was still not achieved. Among the main difficulties reported are the complex articulation between different levels of care providers, the low number of orthoptic technician in the national health system, the high burden that images grading, and treatment of positive cases represents for hospitals ophthalmology services, and low adherence rates. Yet, the comparison between strategies adopted in the different regions allowed the identification of potential solutions: hire orthoptic technician for primary health care units, eliminating the dependence of hospital professionals; use artificial intelligence algorithms for automatic retinographies grading, avoiding ophthalmologists overload; adoption of proximity strategies, as the use of portable retinographers, to promote adherence to screening. Conclusion: Access to diabetic retinopathy screening remains remarkably variable in Portugal and needs urgent attention. However, several characteristics of effective screening programmes were found in Portuguese screening programmes, what seems to point toward promising outcomes, especially if each other highlights are considered. The findings of this research could be very useful for the other countries with similar socio-political characteristics.